Perceived Corruption and Economic Growth: A World Panel Data Analysis - Mochamad Taufiq Ariq Purwanto; Alfa Farah (Universitas Negeri Semarang, 2025)
The prevailing view on the impact of corruption on economic growth support the Sand the Wheels argument, namely: corruption impedes economic growth. Corruption increases transaction costs and market certainty. Furthermore, corruption redirects skilled labor from productive towards rent-seeking activities. Corruption also distorts the allocation of government expenditures. Nevertheless, empirical literature on the impact of corruption on economic growth is not unambiguous. Therefore, this study empirically investigates the relationship between corruption and economic growth. This study measures corruption using the Corruption Perception Index (CPI) published annually by Transparency International (TI). Using a sample of 123 countries around the world during the period 2011 to 2018 and the fixed-effects method, the results show that higher corruption is associated with lower economic growth. In specific, a country that can lower its corruption level has a higher level of economic growth. Nevertheless, our heterogenous analysis that classifies country by continent shows that the significant effect remains only in America and Asia-Oceania.